Geographically Explicit Network Analysis of Urban Living and Working Interaction Pattern in Shenzhen City, South China - Yuan, Zhilu; Lin, Haojia; Tang, Shengjun; Guo, Renzhong (Frontiers in Physics, 2021)
Human daily mobility plays an important role in urban research. Commuting of urban residents is an important part of urban daily mobility, especially in working days. However, the characteristic of the mobility network formed by the commuting of urban residents and what impact does it have on the internal structure of the city are still an important works that need to be further explored. Aiming to study the living-working interactions pattern of meta-populations over urban divisions within cities, a fine-grained dataset of living-working tracking of Shenzhen is curated and used to construct an urban living-working mobility network, and the living-working interactions pattern is analyzed through the community structures of network. The results show that human daily mobility plays an important role to understand the formation of urban structure, the administrative divisions of city affect human daily mobility and human daily mobility reacts on the formation of urban structure.